Increased plasma asymmetric dimethylarginine is associated with cognitive deficits in patients with schizophrenia. (30th December 2016) - Yang, Yuan-Jian; Xiong, Jian-Wen; Zhao, Ying; Zhan, Jin-Qiong; Chen, Hai-Bo; Yan, Kun; Hu, Mao-Rong; Yu, Bin; Wei, Bo
Abstract: Cognitive deficits are a core feature of schizophrenia. Previous studies have shown that plasma asymmetric dimethylarginine (ADMA), an endogenous inhibitor of the nitric oxide synthase, was increased in patients with schizophrenia. This study aimed to investigate the association of ADMA with cognitive deficits in schizophrenia. Forty-seven patients with schizophrenia and 45 healthy control subjects were recruited in present study. Cognitive function was assessed with a neuropsychological battery including 7 neurocognitive tests. Schizophrenic symptoms were assessed using the Positive and Negative Syndrome Scale and plasma ADMA concentration was measured by HPLC. We found that patients with schizophrenia exhibited poorer performances in nearly all of the cognitive tests except for the visual memory index compared with healthy controls. Plasma ADMA levels were significantly increased in patients with schizophrenia when compared to normal controls, and the mean ADMA concentration in patients with multiple episode schizophrenia was much higher than that of patients with first episode schizophrenia. For the patients, ADMA was negatively associated with attention, working memory and executive function in schizophrenia. These results suggest that ADMA may be involved in the pathophysiology of schizophrenia-associated cognitive impairments, and plasma ADMA could be a peripheral biomarker for evaluation of cognitive function in schizophrenia. Highlights: Patients with schizophrenia exhibited poorer cognitive performances than controls. Plasma ADMA levels were significantly increased in patients with schizophrenia. Increased ADMA was associated with cognitive impairments in schizophrenia.